2022
DOI: 10.1021/acs.joc.2c01957
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Mechanistic Approach to the Metal-Free N-Alkylation of 2-Aminopyridines with Diketones

Abstract: N-alkylation of amines is an important catalytic reaction in synthetic chemistry. Herein, we report a simple strategy for the N-alkylation of 2-aminopyridines with 1,2-diketones using BF3·OEt2 as a catalyst. The reaction proceeds under aerobic conditions, leading to the formation of a diverse range of substituted secondary amines in good to excellent yields. A close inspection of the mechanistic pathway using various spectroscopic techniques and the computational study revealed that the reaction proceeds throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Reactions performed using 0.002 mmol of compound 1 a and 2 a' with DMF (2.00 ml) as solvent followed by different acid catalysts (3 ml). have reported the synthesis of such heterocycles [49] using H 3 PO 4 , HCl, CH 3 COOH and BF 3 .OEt 2 . However, they have reported the use of BF 3 .OEt 2 with 30 mol % which gave the product with a yield of 77 %.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reactions performed using 0.002 mmol of compound 1 a and 2 a' with DMF (2.00 ml) as solvent followed by different acid catalysts (3 ml). have reported the synthesis of such heterocycles [49] using H 3 PO 4 , HCl, CH 3 COOH and BF 3 .OEt 2 . However, they have reported the use of BF 3 .OEt 2 with 30 mol % which gave the product with a yield of 77 %.…”
Section: Resultsmentioning
confidence: 99%
“…Since, it has the composition of various acids as shown in Figure 1, the mol % was not calculated. Nad et al have reported the synthesis of such heterocycles [49] using H 3 PO 4 , HCl, CH 3 COOH and BF 3 .OEt 2 . However, they have reported the use of BF 3 .OEt 2 with 30 mol % which gave the product with a yield of 77 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations